ANALISIS FAKTOR PENGEMBANGAN DAN DETERMINAN NILAI TAMBAHAN EKONOMI KREATIF DI KABUPATEN KEDIRI - Mayvani, Titov Chuk's (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to determine how the level of development of creative economy businesses from the initial conditions of the business to the current conditions, as well as to find out some of the competitiveness factors that can affect the added value of the creative economy in Kabupaten Kediri. Design/methodology/approach- The sample in this study were creative economy entrepreneurs in Kabupaten Kediri using purposive sampling technique in which there were 84 samples of business actors. The pairwise difference test, while OLS regression analysis was used to analyze the factors that affect the added value of the creative economy . Findings- This research resulted in several findings, there are: (1) the largest creative economy sub-sector in Kabupaten Kediri is culinary, crafts, and performing arts, (2) Several core problems in the development of the creative economy including the lack of integration of the creative economy database, weak institutional functions, low level of product creativity, underdeveloped marketing systems or techniques, and no integration between sub-sectors, (3) there are three sub-sectors. potential to be developed in Kabupaten Kediri, (4) the results show that education and marketing both have a very significant influence in increasing the added value of creative economy entrepreneurs in Kabupaten Kediri. Keywords: creative economy, Kabupaten Kediri